2012
DOI: 10.2174/1874192401206010076
|View full text |Cite
|
Sign up to set email alerts
|

Low Vitamin D and Cardiovascular Risk Factors in Males and Females from a Sunny, Rich Country

Abstract: Background:Low serum vitamin (vit) D levels are common even in sunny countries. We assessed the prevalence and relationship of low vit D with cardiovascular risk factors in Qatar.Methods:Data were collected retrospectively from January 2008 and November 2009. In patients who had low vi t D (< 30 ng/ml ) , demographic and clinical profiles were analyzed and compared in males and females.Results:The overall mean level of vit D among 547 patients was 14.4±11 ng/mL. Among the low vitamin D group, 56% were females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…Several studies have reported VitD deficiency among different populations from the Middle East [12][13][14][15] . A report from Kuwait showed subclinical VitD deficiency among veiled women 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported VitD deficiency among different populations from the Middle East [12][13][14][15] . A report from Kuwait showed subclinical VitD deficiency among veiled women 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The imprecision at 56 and 19 ng/ml as measured by coeicient of variation was 8.7 and 13.2%, respectively [14]'. The Diazyme's 25(OH) D assay is one of the fast track diagnostic methods with complete testing results in less than 2 hours.…”
Section: Methodsmentioning
confidence: 95%
“…Vit D deiciency was deined as level less than 30 ng/ml which was further subdivided into mild (20-29 ng/ml), moderate (10-19 ng/ml) and severe insuiciency (less than 10 ng/ml) [14,21]. Patient characteristics and outcomes were analysed and compared according to the severity of Vit D deiciency.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations